TERRITORIAL SETTLEMENT AND CLAN DIVISIONS OF THE LULIS IN THE SURKHAN OASIS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Over time, the Lulis have migrated to the Surkhan Oasis for various reasons. Their migration routes followed the directions of India–Afghanistan–Uzbekistan, India–Afghanistan–Iran–Afghanistan–Uzbekistan, and India–Afghanistan–Tajikistan–Uzbekistan. The stages of Luli migration into the Surkhandarya Oasis occurred at different historical periods. This article examines the division of the Lulis in the Surkhandarya region into distinct groups, their migration areas, the predominant occupations within these groups, the impact of these professions on their social life, the challenges encountered during their transition from a nomadic to a sedentary lifestyle, and the ethno-demographic and ethno-cultural processes that resulted from their settlement—issues which have not been sufficiently studied so far.